M.NÍZANOV SHÍǴARMALARÍNDA FRAZEOLOGIZMLERDIŃ MORFOLOGIYALÍQ BILDIRLIWI - Sársenbaev, Q. (SCIENCE and SOCIETY, 2019)
The article is devoted to the stylistic use of phraseological units in works of fiction. The author of the article also studies the issues of what parts of speech phraseological units are expressed. They can be expressed by such parts of speech as noums, adverbs and verb. The literary works of the famous Karakalpak writer M.Nizanov became the material for the investigation.